2010
DOI: 10.1177/000348941011900210
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter Analysis of Titanium Vocal Fold Medializing Implant in an Excised Larynx Model

Abstract: Objective Evaluate the efficacy of the titanium vocal fold medializing implant (TVFMI) for the treatment of unilateral vocal fold paralysis (UVFP) based on acoustic, aerodynamic, and mucosal wave measurements in an excised larynx setup. Methods Measurements were recorded on eight excised canine larynges with simulated UVFP before and after medialization with the TVFMI. Results Phonation threshold flow (PTF) and phonation threshold power (PTW) decreased significantly after medialization (p<0.001; p=0.008). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(73 reference statements)
1
10
0
1
Order By: Relevance
“…As observed previously, 10,14 PTF varied significantly across treatments while PTP did not. PTF is directly related to the cube of neutral glottal half-width 15 and is more sensitive than PTP to changes in glottal abduction.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As observed previously, 10,14 PTF varied significantly across treatments while PTP did not. PTF is directly related to the cube of neutral glottal half-width 15 and is more sensitive than PTP to changes in glottal abduction.…”
Section: Discussionsupporting
confidence: 84%
“…Ex vivo canine larynges have been used extensively to study vocal fold paralysis. 10,12-14 There are several anatomical differences in the canine larynx relative to the human, including more angulated thyroid and cricoid cartilages, and the absence of a well-defined vocal ligament. 12 These differences did not affect the procedures performed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several limitations to the experimental design and implant that will be the subject of future investigations. Although the excised larynx setup is a valuable research tool and has been used frequently to study VFP,5, 16, 17, 19, 20 it cannot simulate all clinical concerns of thyroplasty such as physiological tissue response to implant insertion and long‐term effectiveness of the implant. Second, a round balloon was used in this study, which has the natural tendency to expand uniformly in all directions.…”
Section: Discussionmentioning
confidence: 99%
“…[92], who evaluated the efficacy of a titanium vocal fold medializing implant (TVFMI) for the treatment of unilateral vocal fold paralysis on the basis of acoustic, aerodynamic, and mucosal wave measurements in eight excised canine larynges. The authors reported that the phonation threshold flow, phonation threshold power, jitter, and shimmer decreased significantly after medialization.…”
Section: Excised Human and Animal Larynx Experimentsmentioning
confidence: 99%